2021
DOI: 10.1038/s41598-021-93173-0
|View full text |Cite
|
Sign up to set email alerts
|

Physical processes controlling the diurnal cycle of convective storms in the Western Ghats

Abstract: Diurnal variation of convective storms (CSs) during monsoon season and associated physical mechanisms are significantly important for accurate forecast of short-time and extreme precipitation. The diurnal cycle of CSs is investigated using ground-based X-band radar, Tropical Rainfall Measuring Mission Precipitation Radar, and reanalysis data during the summer monsoon (June–September of 2014) over complex mountain terrain of Western Ghats, India. Diurnally, CSs show a bimodal distribution in the coastal areas, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Krishna et al. (2021) have recently showed that in the leeward side (a rain shadow region), the convection is dominated by the diurnal cycle of surface heating. All these supports the present findings in Figure 6 that storms associated with lightning have a larger propensity of high occurrence mostly over the leeward side of WG compared to the windward side.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Krishna et al. (2021) have recently showed that in the leeward side (a rain shadow region), the convection is dominated by the diurnal cycle of surface heating. All these supports the present findings in Figure 6 that storms associated with lightning have a larger propensity of high occurrence mostly over the leeward side of WG compared to the windward side.…”
Section: Resultsmentioning
confidence: 99%
“…From this it may be inferred that the higher (lower) percentages of intense convective cores are generally found in the regions of low (high) overall storm occurrence (see their Figure 2a). Krishna et al (2021) have recently showed that in the leeward side (a rain shadow region), the convection is dominated by the diurnal cycle of surface heating. All these supports the present findings in Figure 6 that storms associated with lightning have a larger propensity of high occurrence mostly over the leeward side of WG compared to the windward side.…”
Section: Spatial Distributionmentioning
confidence: 99%
“…Based on the data collected at HACPL by the various in-situ instruments, some studies in the past performed to understand cloud-aerosol interaction over the Western Ghats (Anil Kumar et al, 2016;Buchunde et al, 2019;Das et al, 2017Das et al, , 2020Jayachandran et al, 2018;Konwar et al, 2010Konwar et al, , 2014Krishna et al, 2021;Kumar et al, 2022;Kumar & Silva, 2019;Leena et al, 2016Leena et al, , 2018Leena et al, , 2021Mukherjee et al, 2018;Singla et al, 2017;Sumesh et al, 2019Sumesh et al, , 2021Utsav et al, 2017;Varghese et al, 2021;. To study the diurnal variation of DSD, we use an impact-based disdrometer, i.e., Joss-Waldvogel Disdrometer (JWD) (Joss & Waldvogel, 1969) measurements during the Indian Summer Monsoon (ISM: June, July, August and September month) period between 2015 and 2019 at the HACPL, Mahabaleshwar, which is situated in the windward side of the Western Ghats in India.…”
Section: Joss-waldvogel Disdrometermentioning
confidence: 99%
“…The 0000 UTC soundings are used to classify the different phases of F. The 0000 UTC soundings are chosen for the following reasons. The peak of the diurnal cycle of rainfall over the Western Ghats is around 1030 UTC (1600 LST: (Flynn et al, 2017;Krishna et al, 2021)), thus, the 1200 UTC soundings, on most days, will reflect the conditions over the coast shortly after the peak rainfall events. Second, we believe that the nocturnal to early morning anomalous land/valley breeze is a key element in the offshore propagation of rainfall.…”
Section: Phases Of Fmentioning
confidence: 99%